Tracking forest dynamic trends in Belize: the role of protected areas, agriculture, and fire in the South Eastern Selva Maya. Issue 8 (3rd August 2022) - Green, Kasyan; Rogan, John; Sauls, Laura; Cuba, Nicholas; Pennell, Roberta Kamille; Bebbington, Denise
ABSTRACT: The Selva Maya represents the largest expanse of tropical forest in Mesoamerica, encompassing parts of Belize, northern Guatemala, and south-eastern Mexico. Patterns and processes of forest loss in Belize are less comprehensively studied than other regions in the Selva Maya. Hence, this research tracks twenty years of forest loss in relation to Protected Areas (PAs) and transborder activity in the country. Results show that since 2000, Belize lost 11% of its forest cover. In that same period, 39.7% of this loss has seen forest recovery, predominantly in southern portion of the country, and within PAs. Ongoing forest loss in the north has expanded towards central and southern Belize. Forest loss in PAs account for 14.3% of overall loss nationwide, with fires and agricultural expansion playing a prominent role in the encroachment on forestland. A better understanding of forest loss in Belize reinforces distinctions between forest loss in the north and the south of the country and demonstrates the need for enhanced forest protection. This research provides new information to conservation planners to better understand the dynamics and drivers of forest loss and regrowth in the Selva Maya region.